PERFORMANCE COMPARISON ANALYSIS BETWEEN RSS AND CONVENTIONAL MUD MOTOR IN MAVVAR FIELD - Raka Sudira Wardana; Bastian Andoni (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
Rotary Steerable System (RSS) has transformed the directional drilling industry by producing smoother borehole, reducing torque and drag and enhancing the Rate Of Penetration (ROP). Despite the advantages of using RSS, the conventional steerable motor is still widely used in deviated well due to its lower daily cost. Therefore, to optimize the performance and the cost of the drilling operation, it is critical to analyze when the RSS outweigh the conventional mud motor. This paper analyzes the performance between Rotary Steerable System and Conventional Steerable Motor, based on these following parameters: Rate of Penetration (ROP), overall drilling cost, borehole quality and lost in hole cost. This empirical study uses literature study and quantitative data analysis from several wells in Mavvar Field in compliment. The result shows that the Rotary Steerable System (RSS) provides better performance and more efficient in cost.